Engineering Spatial Ability and Spatial Geometry – Research Experiences 1. - Nagyné Kondor, Rita (International Journal of Engineering and Management Sciences, 2018)
Spatial visualization skills have an important role in teaching and learning of engineering studies. Many studies have shown that there are correlations between various measures of spatial skills and performance in particular Science, Technology, Engineering and Mathematics (STEM). Many engineering students have problems with imagining a spatial figure and therefore to solve the spatial geometry exercises, so development of spatial ability is very important. We have developed special tools and worksheets for development of spatial abilities